Annealing method for improving performance of large-size crystal material

By using a zirconia-homogeneous polycrystalline composite landfill material and a CO-CO2-Ar mixed atmosphere, the problem of temperature non-uniformity during annealing was solved, improving the optical and mechanical properties of large-size crystal materials, especially the ultraviolet-visible light transmittance and thermal shock resistance.

CN121344775APending Publication Date: 2026-01-16TDG HLDG CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511518514.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-23
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

The uneven temperature field in existing annealing furnaces leads to temperature differences within and between large-size crystal materials, causing stress differences and microstructural distortions, which affect the consistency of optical and mechanical properties. Existing embedding materials are either not adaptable to large-size wafers or are too complex to operate.

Method used

By using zirconia-homogeneous polycrystalline composite landfill material and a CO-CO2-Ar mixed atmosphere, temperature uniformity during annealing is ensured through matching thermal expansion coefficients, thermal buffering, and oxygen vacancy control. Combined with the reversible redox reaction of CO-CO2, alumina decomposition is suppressed, reducing the risk of thermal shock.

Benefits of technology

It significantly improves the UV-Vis light transmittance and thermal shock resistance of large-size crystal materials, reduces microcracks and dislocations, and improves optical uniformity and mechanical properties, making it suitable for LED substrates and optical window materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121344775A_ABST
    Figure CN121344775A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of crystal material processing, in particular to an annealing method for improving the performance of a large-size crystal material, which takes a zirconium oxide-isomorphic source polycrystalline material composite landfill material as an annealing medium and a CO-CO2-Ar mixed gas as an annealing atmosphere. Wherein the thermal buffer provided by the isomorphic source polycrystal material can realize the smooth transition of the temperature gradient and reduce the heat flux density; the zirconium oxide material is low in thermal conductivity, a thermal resistance layer can be formed, and microcracks caused by rapid thermal shock are reduced. Dynamic balance of oxygen partial pressure can be achieved through reversible conversion of CO-CO2 in the mixed gas, reaction gas is further diluted through Ar, and decomposition of aluminum oxide and formation of oxygen vacancies are effectively inhibited. The method effectively solves the problem of uneven heating caused by large temperature gradient during annealing of a large-size crystal material in the prior art, further improves the thermal shock resistance of the material, reduces microdefects, improves the crystal transmittance and eliminates stress.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of crystal material processing, and particularly relates to an annealing method for improving the performance of large-size crystal materials. BACKGROUND

[0002] Annealing is a kind of heat treatment process, which is a key step in wafer manufacturing. By heating the wafer to a certain temperature and keeping it at the temperature for a period of time, and then cooling it at a controlled speed, the stress can be relieved, the lattice defects can be repaired, the doping ions can be activated, and the mechanical and optical properties of the material can be improved. The whole annealing process is usually carried out in a special high-temperature annealing furnace. The power of the annealing furnace is precisely controlled by PID to realize the temperature stability and uniform distribution in the furnace cavity. However, the existing annealing furnace temperature field is limited by the spatial physical layout of the heater, which causes large temperature gradient differences in each region, resulting in inconsistent conduction heat rates at each point, causing temperature differences in the crystal material sample and between the samples, thereby causing certain stress differences in the sample interior or between the samples, and also causing the microstructure of the sample interior to be distorted or scattered, dislocation migration, and other microdefects to occur, thereby leading to poor consistency of the optical or mechanical properties of the sample.

[0003] To solve this problem, the filling material used in the Chinese patent “Gallium oxide wafer stress relief annealing method” with publication number CN105200526A is gallium oxide crystal powder of the same material as the crystal to be annealed, which avoids direct exposure of the wafer surface and plays a role in protecting the wafer surface quality. Combined with nitrogen protection, the uniformity of the thermal field is emphasized. This patent only eliminates macroscopic stress and does not involve the repair of microscopic defects such as oxygen vacancies or dislocations; it is not suitable for large-size wafers and may affect the heat conduction efficiency.

[0004] The filling material used in the Chinese patent “Annealing method of neodymium, cerium and chromium doped yttrium aluminum garnet crystal” with publication number CN103409806A is aluminum oxide powder, which is used in combination with argon protection to eliminate scattered particles and stress. The use of aluminum oxide powder filling has a difference in thermal expansion coefficient (8×10 -6 / ℃) from yttrium aluminum garnet (7×10 -6 / ℃), which may cause interface stress accumulation during the annealing process and trigger microcracks or dislocation proliferation.

[0005] The Chinese patent CN104695025A, entitled "Equipment for Rapid Heating and Annealing of CaF2 Crystals with Thermal Shock Resistance," uses a composite filler material (CaF2 polycrystalline particles + thermally conductive particles (graphite particles, hot-pressed BN particles, or metallic Mo particles) + 1-4 wt% ZnF2 powder). This mixed polycrystalline particle filler resists thermal shock from the external environment, primarily improving thermal inertia and oxidation resistance. The heating and cooling rates are controlled by a dual heating system (internal and external temperature field switching). However, the thermal conductivity of the thermally conductive particles in this patent differs significantly from that of CaF2 (e.g., graphite has a thermal conductivity of approximately 100-2000 W / (m·K), while CaF2 has only about 9 W / (m·K)), which may lead to uneven local temperature gradients. Furthermore, the dual heating system is complex to operate, requiring precise control of the switching timing, and is susceptible to thermal shock due to human error. Summary of the Invention

[0006] This invention provides an annealing method to improve the performance of large-size crystal materials. The crystal is annealed using a composite filling material of "zirconia-polycrystalline material from the same source" and a mixed gas protective atmosphere. The whole process has the functions of thermal expansion matching, oxygen vacancy regulation and thermal buffering. The innovation lies in the synergistic effect of the combination of materials and mixed atmosphere, which ensures that the entire crystal is heated uniformly during the annealing process. The core ideas are as follows: (1) The polycrystalline material from the same source has the same coefficient of thermal expansion as the material to be annealed. There is no shear stress accumulation at the interface during the heating / cooling process, which avoids dislocation proliferation in the crystal. The thermal buffer of the polycrystalline material from the same source can realize a smooth transition of temperature gradient and reduce heat flux density. (2) At the same time, the thermal conductivity of zirconia material is low (2-3 W / (m·K)). The thermal resistance layer formed during the annealing process can play a high thermal insulation role and reduce microcracks caused by rapid thermal shock in the crystal. The composite landfill material utilizes the synergistic effect of the physical properties of two high-temperature resistant materials, zirconium oxide and polycrystalline material from the same crystal source, to achieve thermal field uniformity without a complex heating system. This effectively solves the problem of uneven heating caused by annealing of large-size crystal materials, reduces internal stress difference, improves the thermal shock resistance of the material, and reduces microscopic defects. (3) Combined with the annealing atmosphere of CO-CO2-Ar mixed gas, oxygen vacancies and alumina decomposition are further suppressed, scattering centers are reduced, and the ultraviolet-visible light transmittance of sapphire is significantly improved.

[0007] An annealing method for improving the properties of large-size crystal materials includes the following steps:

[0008] Step 1: In the annealing container, cover the material to be annealed with composite filling material, and then cover the annealing container with the lid.

[0009] Step 2: Place the annealing container filled with composite landfill material and the material to be annealed vertically in the annealing furnace and anneal in a CO-CO2-Ar mixed gas atmosphere;

[0010] In step one, the composite landfill material is composed of zirconium oxide and polycrystalline material from the same crystal source as the material to be annealed. The purity of both the polycrystalline material and zirconium oxide is 99% or higher, and the size is 0.5-50mm granules. The two have different particle sizes and should be distinguished. For example, the particle size of zirconium oxide is 20mm and the particle size of the polycrystalline material from the same crystal source is 10mm. The purpose is to facilitate the rapid and thorough separation of the polycrystalline material from the same crystal source and zirconium oxide after annealing, so as to achieve recycling.

[0011] Furthermore, the composition of the composite landfill material varies at different depths within the annealing container: at the bottom of the annealing container, the material in direct contact with the material to be annealed is 100wt% homocrystalline polycrystalline material. As the depth decreases, the mass percentage of homocrystalline polycrystalline material in the composite landfill material decreases linearly, while the mass percentage of zirconium oxide increases linearly, until the top of the annealing container is 100wt% zirconium oxide.

[0012] In this process, the bottom of the annealing container uses polycrystalline material from the same crystal source to directly contact the material to be annealed. The thermal expansion coefficient of the same material can effectively reduce interfacial stress. The top of the annealing container utilizes the high thermal insulation and chemical inertness of zirconium oxide to effectively reduce microcracks in the crystal caused by rapid thermal shock. This composite landfill material, which is a gradual mixture of polycrystalline material from the same crystal source and zirconium oxide from the bottom to the top of the annealing container, can effectively avoid stress concentration caused by abrupt interface changes.

[0013] In step one, the total thickness of the composite landfill material is 1.5-2 times the total thickness of the material to be annealed. If the total thickness of the composite landfill material is too large, it may introduce impurities, and if it is too small, it will weaken the stress buffering effect.

[0014] In step one, the material to be annealed is sapphire, and its specifications can be one or more combinations of crystal blocks, crystal rods and wafers;

[0015] In step one, the annealing container can be a sagger or a crucible.

[0016] In step two, annealing is carried out in a mixed gas atmosphere of CO-CO2-Ar, with a flow rate of 5-8 L / min, which can further control the introduction of impurities.

[0017] The total volume fraction of CO and CO2 is 5 vol%-6.5 vol%, CO:CO2=1:(7-15), and the remainder is Ar;

[0018] In step two, the annealing process includes a heating stage, a constant temperature stage, and a cooling stage. The heating stage involves heating from room temperature to 1200-1800℃ at a rate of 1-5℃ / min; the constant temperature stage involves holding at 1200-1800℃ for 12-36 hours; and the cooling stage involves cooling from 1200-1800℃ to room temperature at a rate of 0.5-3℃ / min.

[0019] The highest annealing temperature should be at least 100°C lower than the polycrystalline material of the same crystal source and the lower softening point of zirconium oxide in the composite landfill material. For example, if the softening point temperature of sapphire crystal is 1900°C and the softening point temperature of zirconium oxide is 2000°C, then the annealing temperature of sapphire crystal should not be higher than 1800°C.

[0020] In step two, during annealing, waste crystal rods are used to suspend the annealing container.

[0021] An annealing method for improving the properties of large-size crystal materials further includes the following steps:

[0022] After the annealed crystal material is chamfered and polished, its transmittance and stress birefringence performance can be tested once the roughness meets the requirements.

[0023] The beneficial effects of this invention are:

[0024] (1) Using a CO-CO2-Ar mixed gas as the annealing atmosphere, a dynamic thermodynamic equilibrium is established through the reversible redox reaction of CO-CO2 (CO2←→CO+½O2). By precisely controlling the oxygen partial pressure of the system, the decomposition of alumina material can be effectively suppressed, and the formation of oxygen vacancy defects can be prevented. Ar, as an inert gas, dilutes the concentration of the reaction gas, reduces the reaction rate of CO and O2, and further slows down the consumption of oxygen. The CO-CO2 mixed gas suppresses the decomposition reaction through thermodynamic equilibrium, maintains the integrity of the crystal, reduces scattering loss, and significantly improves the ultraviolet-visible light transmittance of the material.

[0025] (2) The annealing method using the composite landfill material of "polycrystalline material with the same source + zirconium oxide" ensures that the thermal expansion coefficients of the polycrystalline material at the bottom of the annealing container and the material to be annealed are completely matched, avoiding the accumulation of interfacial shear stress and allowing the temperature gradient to transition naturally and smoothly during the heating and cooling process; the zirconium oxide at the top forms a low thermal conductivity layer, reducing the risk of thermal shock caused by rapid heating or cooling. The composite landfill material significantly reduces the probability of microcracks and increases the thermal shock resistance of the material through the thermal buffering effect of the polycrystalline material with the thermal insulation barrier effect of zirconium oxide; and the uniformity of the thermal field during the annealing process is conducive to promoting the orderly migration of atoms, eliminating lattice distortion and dislocations, and improving the dislocation density and optical uniformity of the sapphire substrate.

[0026] (3) The two technologies are combined to control oxygen vacancies and repair lattice defects by layered composite burial at high temperature through reducing atmosphere. This mainly improves defects such as color centers and dislocations in sapphire. The core principle is to balance oxygen vacancy concentration and lattice integrity, thereby reducing material stress and improving transmittance. It is suitable for LED substrate preparation and optical window materials. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of an annealing apparatus for composite landfill materials, where: 1-composite landfill material, 2-material to be annealed, 3-annealing furnace, 4-annealing container;

[0028] Figure 2 This is a flowchart of the method in Example 1;

[0029] Figure 3 Here is the flowchart of the method in Comparative Example 1;

[0030] Figure 4 Here is the flowchart of the method in Comparative Example 2;

[0031] Figure 5 This is a comparison chart of the ultraviolet transmittance of the wafers obtained in Example 1 and Comparative Examples 1-2;

[0032] Figure 6 This is a comparison chart of the visible light transmittance of the wafers obtained in Example 1 and Comparative Examples 1-2;

[0033] Figure 7 The image shows the stress birefringence test results of the wafer obtained in Example 1;

[0034] Figure 8 The image shows the stress birefringence test results of the wafer obtained in Comparative Example 1.

[0035] Figure 9 The image shows the stress birefringence test results of the wafer obtained in Comparative Example 2. Detailed Implementation

[0036] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0037] Example 1

[0038] An annealing method for improving the properties of large-size crystal materials employs a composite annealing process under a CO-CO2-Ar mixed gas atmosphere. Figure 2 As shown, it includes the following steps:

[0039] (1) Wire cutting: Select a 6-inch sapphire substrate crystal rod and cut it directly according to the process settings. Select wafers from the head, middle and tail of the crystal rod.

[0040] (2) Double-sided grinding: The wafer obtained in (1) is ground to remove the cutting damage layer caused during slicing and improve the flatness of the wafer. After grinding, it is cleaned to obtain the wafer to be annealed.

[0041] (3) Annealing of composite embedded wafers:

[0042] Step 1: Thoroughly clean the crucible using a vacuum cleaner to minimize the impact of contaminants on the sample surface morphology during annealing. First, lay a layer of homocrystalline polycrystalline material (fine-grained sapphire polycrystalline material) with a particle size of 10mm at the bottom of the crucible. Place all the wafers to be annealed sequentially on this polycrystalline material layer in a stacked manner, and continue to ensure complete contact and embedding with the wafers using homocrystalline polycrystalline material. The thermal expansion coefficient of the fine-grained sapphire polycrystalline material matches that of the wafers, which helps to achieve a smooth temperature transition and reduce thermal stress. Subsequently, continue filling with composite embedding material 1. The mass percentage of homocrystalline polycrystalline material in composite embedding material 1 decreases linearly, while the mass percentage of zirconium oxide increases linearly, until the top layer is entirely composed of zirconium oxide (particle size 20mm). This gradient structure utilizes the thermal buffering properties of homocrystalline polycrystalline material and the thermal barrier effect of zirconium oxide to synergistically enhance thermal shock resistance and effectively suppress thermal shock. After embedding, cover the crucible with the lid.

[0043] Step 2: Open the furnace door of annealing furnace 3, clean the furnace chamber with a vacuum cleaner, and vertically place the sagger containing the wafers and composite embedding material 1 obtained in Step 1 into annealing furnace 3. Use scrap crystal rods to support the sagger for annealing. Before annealing, evacuate the furnace, then introduce a CO-CO2-Ar mixed gas at a flow rate of 7 L / min, where the total volume fraction of CO and CO2 is 6 vol%, and CO:CO2 = 1:10. The specific annealing process is as follows: During the heating stage, the temperature is increased from room temperature to 1450℃ at a rate of 3℃ / min; during the isothermal stage, the temperature is held at 1450℃ for 24 hours; during the cooling stage, the temperature is slowly reduced to room temperature at a rate of 1.5℃ / min.

[0044] (4) Chamfering: The outer edge of the annealed wafer obtained in (3) is chamfered to improve the mechanical strength of the wafer edge, avoid stress concentration, and avoid abnormalities such as edge chipping in subsequent processing;

[0045] (5) Polishing: Polishing liquid and polishing pad are used on the chamfered wafer obtained in (4), and the appropriate temperature, pressure and rotation speed are used to polish the wafer to eliminate the mechanical / chemical damage layer left by the previous process, improve the surface roughness of the wafer, and obtain a wafer with excellent surface flatness.

[0046] (6) Performance testing: The optical transmittance and stress birefringence of the processed wafers are tested.

[0047] Comparative Example 1

[0048] Annealing in a CO-CO2-Ar mixed gas using a single zirconium oxide burial method, such as... Figure 3 As shown, it includes the following steps:

[0049] (1) Line cutting: Same as in Example 1;

[0050] (2) Double-sided grinding: Same as in Example 1;

[0051] (3) Single zirconium oxide landfill annealing:

[0052] Step 1: Thoroughly clean the crucible with a vacuum cleaner to minimize the impact of contaminants on the sample surface morphology during annealing. Place a layer of zirconium oxide at the bottom of the crucible, then stack the wafers to be annealed in sequence, completely covering them with zirconium oxide to ensure even heating and provide a buffer. After completely covering the wafers with zirconium oxide, replace the crucible lid.

[0053] Step 2: Open the furnace door of annealing furnace 3, clean the furnace chamber with a vacuum cleaner, and place the sagger containing the wafers and zirconium oxide obtained in Step 1 vertically in annealing furnace 3. Use scrap crystal rods to support the sagger for annealing. Before annealing, evacuate the furnace, then introduce a CO-CO2-Ar mixed gas at a flow rate of 7 L / min, with a total volume fraction of 6 vol% for CO and CO2, and a CO:CO2 ratio of 1:10. The specific annealing process is as follows: During the heating stage, the temperature is increased from room temperature to 1450℃ at a rate of 3℃ / min; during the isothermal stage, the temperature is held at 1450℃ for 24 hours; during the cooling stage, the temperature is slowly reduced to room temperature at a rate of 1.5℃ / min.

[0054] (4) Chamfering: Same as in Example 1;

[0055] (5) Polishing: Same as in Example 1;

[0056] (6) Performance testing: Same as in Example 1.

[0057] Comparative Example 2

[0058] Without annealing, such as Figure 4 As shown, it includes the following steps:

[0059] (1) Line cutting: Same as in Example 1;

[0060] (2) Double-sided grinding: Same as in Example 1;

[0061] (3) Chamfering: Same as in Example 1;

[0062] (4) Polishing: Same as in Example 1;

[0063] (5) Performance testing: Same as in Example 1.

[0064] The performance test results of the wafers obtained in Example 1 and Comparative Examples 1-2 were analyzed as follows:

[0065] The transmittance test results of the wafers obtained in Example 1 and Comparative Examples 1-2 are as follows: Figure 5 and 6 As shown, regardless of whether it is in the ultraviolet or visible light band, the transmittance of the wafer obtained by annealing with the composite landfill material of Example 1 combined with CO-CO2-Ar mixed atmosphere is significantly improved, and the transmittance improvement is particularly significant in the ultraviolet band (250-400nm), where the transmittance can reach 85%, while the transmittance of the wafer obtained by annealing with single zirconia in Comparative Example 1 is only 80%.

[0066] Comparative Example 2, the non-annealed control group, exhibited strong absorption in the 200-235nm wavelength range. This strong absorption is mainly due to oxygen vacancies generated during crystal growth or processing. While annealing significantly improves the ultraviolet transmittance of the wafers, Comparative Example 1, after annealing in a CO-CO2-Ar mixed atmosphere combined with single zirconia embedding, showed differences in transmittance across the head, middle, and tail of the crystal rod, resulting in a relatively wide transmittance distribution. In contrast, Example 1, after annealing in a CO-CO2-Ar mixed atmosphere combined with composite embedding, showed no significant differences in the wafers across the head, middle, and tail of the crystal rod, and the uniformity and concentration of data between samples were significantly improved. The CO-CO2 mixed gas inhibits decomposition reactions through thermodynamic equilibrium, maintaining crystal integrity, reducing scattering loss, and improving transmittance. Combined with the composite embedding method, the same thermal expansion coefficient of the polycrystalline material from the same crystal source reduces interfacial stress, and the high blocking properties of zirconia suppress the formation of internal impurities during annealing. Reduced defects lead to increased transmittance.

[0067] The stress birefringence test results of the wafers obtained in Example 1 and Comparative Examples 1-2 are as follows: Figures 7-9 As shown in Table 1, the stress birefringence data are detailed in Table 1. It can be seen that after the composite material was buried and annealed in a CO-CO2-Ar mixed atmosphere in Example 1, the stress of the wafer was significantly reduced, and the internal stress was effectively eliminated.

[0068] Table 1. Stress birefringence data for Example 1 and Comparative Examples 1-2

[0069] Among these, the stress values ​​of wafers obtained by annealing are lower than those obtained by non-annealing. Furthermore, wafers annealed in a CO-CO2-Ar mixed atmosphere with composite material filling exhibit lower stress and better intra-wafer uniformity compared to wafers annealed with single zirconia in a CO-CO2-Ar mixed atmosphere. This is because, under the filling of a composite material whose composition gradually changes with the depth of the sagger, the uniform temperature field causes dislocations inside the crystal to rearrange through climb and slip, reducing lattice distortion, lowering birefringence, and improving optical uniformity. Matching the coefficients of thermal expansion brings the interfacial strain close to zero, achieving stress elimination. Argon in the CO-CO2-Ar mixed gas provides inert protection, while CO maintains a reducing atmosphere. At high temperatures, dislocations climb (reorganize), reducing dislocation density, and lattice atoms relax local stress through diffusion, improving crystal integrity and further reducing internal stress differences.

[0070] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An annealing method for improving the properties of large-size crystal materials, characterized in that, Includes the following steps: Step 1: In the annealing container (4), the material to be annealed (2) is covered with composite landfill material (1), which is composed of zirconium oxide and polycrystalline material of the same crystal source as the material to be annealed (2); Step 2: Anneal the annealing container (4) containing the composite landfill material (1) and the material to be annealed (2) in a CO-CO2-Ar mixed gas atmosphere.

2. The annealing method for improving the properties of large-size crystal materials as described in claim 1, characterized in that, In step one, the purity of zirconium oxide and polycrystalline material from the same crystal source in the composite landfill material (1) is not less than 99%, and the size is 0.5~50mm granules. The particle size of zirconium oxide and polycrystalline material from the same crystal source are different.

3. The annealing method for improving the properties of large-size crystal materials as described in claim 1, characterized in that, In step one, the composition of the composite landfill material (1) at different depths in the annealing container (4) is different: the bottom part that is in direct contact with the material to be annealed (2) is 100wt% homocrystalline polycrystalline material. As the depth decreases, the mass percentage of homocrystalline polycrystalline material decreases linearly, and the mass percentage of zirconium oxide increases linearly until the top part is 100wt% zirconium oxide.

4. The annealing method for improving the properties of large-size crystal materials as described in claim 1, characterized in that, In step one, the total thickness of the composite landfill material (1) is 1.5-2 times the total thickness of the material to be annealed (2).

5. The annealing method for improving the properties of large-size crystal materials as described in claim 1, characterized in that, In step one, the annealing container (4) is one of the sagger or crucible and is equipped with a cover.

6. The annealing method for improving the properties of large-size crystal materials as described in claim 1, characterized in that, In step two, waste crystal rods are used to suspend the annealing container (4) in the annealing furnace (3).

7. The annealing method for improving the properties of large-size crystal materials as described in claim 1, characterized in that, In step two, a vacuum is first drawn before the mixed gas is introduced. The annealing includes heating, constant temperature and cooling stages: the temperature is raised from room temperature to 1200-1800℃ at a rate of 1-5℃ / min, then kept at a constant temperature for 12-36 hours, and finally cooled to room temperature at a rate of 0.5-3℃ / min.

8. The annealing method for improving the properties of large-size crystal materials as described in claim 1, characterized in that, In step two, the flow rate of the CO-CO2-Ar mixed gas is 5-8 L / min, wherein the total volume fraction of CO and CO2 is 5 vol%-6.5 vol%, CO:CO2=1:(7-15), and the remainder is Ar.

9. The annealing method for improving the properties of large-size crystal materials as described in claim 1, characterized in that, It also includes the following steps: The annealed crystalline material is processed and then its performance is tested. The processing includes chamfering and polishing, and the performance testing includes transmittance testing and stress birefringence testing.

10. The annealing method for improving the properties of large-size crystalline materials as described in any one of claims 1-9, characterized in that, The material to be annealed (2) is sapphire, and the specifications are one or a combination of ingots, rods and wafers.

Citation Information

Patent Citations

  • Annealing method of neodymium, cerium and chromium doped yttrium aluminum garnet crystal

    CN103409806A

  • Thermal shock-resistant rapid-heating CaF2 crystal annealing apparatus

    CN104695025A

  • Gallium oxide wafer stress relieving annealing method

    CN105200526A